A game of thrones : the graphic novel. volume 3 - Abraham, Daniel (Bantam Books, 2014)
The kingdom of the Stark family faces its ultimate challenge in the onset of a generation-long winter, the poisonous plots of the rival Lannisters, the emergence of the Neverborn demons, and the arrival of barbarian hordes.